Kỹ thuật phần mềm - Pressman, Roger S (McGraw-Hill Education, 2015)
Includes bibliographical references (pages 909-932) and index; The software process -- Modeling -- Quality management -- Managing software projects -- Advanced topics; TI079; TI069; TI146; TI064; TI076; TI170